2014
DOI: 10.1063/1.4898786
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared response of reduced graphene oxide and its high-temperature coefficient of resistance

Abstract: Much effort has been made to study the formation mechanisms of photocurrents in graphene and reduced graphene oxide films under visible and near-infrared light irradiation. A built-in field and photo-thermal electrons have been applied to explain the experiments. However, much less attention has been paid to clarifying the mid-infrared response of reduced graphene oxide films at room temperature. Thus, mid-infrared photoresponse and annealing temperature-dependent resistance experiments were carried out on red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 36 publications
(71 reference statements)
0
29
0
Order By: Relevance
“…This behavior of the samples is probably connected to different oxygen functional groups and defects present after different reduction methods of the rGO materials used. It was shown that a high absorption in MIR is obtained for reduced graphene oxide having aggregated oxygen atoms at the edges of defects [32]. Using different reduction methods might lead to formation of different oxygen atoms' arrangement in the carbon structure resulting in their ability to absorb MIR radiation.…”
Section: Polymer Nanocomposites Characterisationmentioning
confidence: 99%
“…This behavior of the samples is probably connected to different oxygen functional groups and defects present after different reduction methods of the rGO materials used. It was shown that a high absorption in MIR is obtained for reduced graphene oxide having aggregated oxygen atoms at the edges of defects [32]. Using different reduction methods might lead to formation of different oxygen atoms' arrangement in the carbon structure resulting in their ability to absorb MIR radiation.…”
Section: Polymer Nanocomposites Characterisationmentioning
confidence: 99%
“…In 2014, Haifeng Liang has reported mid-IR photoresponse of rGO with a responsivity of 1 A/W 17 . Very recently, pristine graphene based infrared photodetectors are demonstrated with an optical modulation of up to 40 GHz, however a low responsivity (~6.1 mA/W), caused by rapid photocarrier dynamics, is compromised 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Bolometric temperature rise of RGO can also lead to generation of photocurrent. [38,39] In order to shed light on this, we studied the effect of temperature on electrical properties of the devices and measured the temperature rise by irradiation ( Figure S7 and Table S1). No appreciable rise in temperature (< 0.1 degree) could be detected (with a resistance temperature detector, resolution of 0.1 K) for ~50 s exposure of infrared radiation (~ mW.cm -2 ).…”
Section: Methodsmentioning
confidence: 99%